Linguodidactic potential of museum texts in teaching Russian as a foreign language (based on the material of the I.V. Savitsky State Museum of Arts) - Genzhebaeva, Gulbakhar Kurbanbaevna (The Lingua Spectrum, 2026)
The article explores the linguodidactic potential of museum discourse in teaching Russian as a foreign language within the context of modern language education. Particular emphasis is placed on the communicative-activity approach, which involves the use of authentic materials and the simulation of real-life communication situations. The empirical basis of the study includes texts from the State Museum of Arts of the Republic of Karakalpakstan named after I.V. Savitsky, such as exhibition descriptions, экскурсионные commentaries, and announcements The research methodology combines literature review, discourse analysis, content analysis, and pedagogical modeling. The paper identifies the multi-level structure of museum discourse, including nominative, interpretative, and communicative-pragmatic levels, and demonstrates its applicability for developing various language skills: listening, speaking, reading, and writing. A system of exercises is presented to ensure the gradual formation of communicative competence, moving from receptive to productive language activities. Special attention is given to culturally marked vocabulary and intercultural communication, as well as to the integration of museum materials with digital educational technologies. The findings confirm that museum discourse is an effective tool for enhancing linguistic and sociocultural competence, increasing learner motivation, and fostering critical thinking skills in foreign language education.